The influence of social media on stakeholder engagement and the corporate social responsibility of small businesses. (30th June 2021) - Khanal, Ananda; Akhtaruzzaman, Muhammad; Kularatne, Indrapriya
Abstract: In recent decades, the concepts of corporate social responsibility (CSR) and social media have gained immense importance among businesses and their stakeholders. These concepts have gained popularity and acceptance among both large and small businesses of most industries. However, the existing CSR literature showed that most studies concentrated on large businesses, leaving the domain of small businesses under‐explored. The literature review revealed that only a few researchers had investigated the influence of social media on stakeholder engagement and the CSR of small businesses. This research aimed to explore the impacts of social media on the CSR of small businesses and used a concurrent mixed‐method research design, employing survey questionnaires from 82 participants and semi‐structured interviews with eight participants. The study conducted among the owners and managers of small businesses in a local government district in New Zealand discovered that many of them considered social media beneficial to engage with stakeholders and understand CSR trends. It also found that social media encouraged businesses to understand their vision, values and implement policies that are environmentally friendly and beneficial to the employees.